Method for preparing Fenton-like catalyst from chestnut shells and application of Fenton-like catalyst in water purification
Through a two-step alkali-activated chestnut shell pyrolysis carbon, a Fenton-like catalyst with high catalytic performance was prepared, which solved the problem of difficult to efficiently degrade phenolic pollutants in the prior art, and achieved an efficient and economical water purification effect.
Patent Information
- Application Number
- CN202411830623.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to direct the introduction of active sites in a simple and economical way, and prepare efficient pyrolysis carbon catalysts for degrading phenolic pollutants.
The pyrolytic charcoal of chestnut shell was activated by a two-step method, and rich surface oxygen-containing functional groups and defect sites were introduced to prepare a Fenton-like catalyst with highly graphitized. This catalyst achieves catalytic degradation of phenolic pollutants through its combination with bisulfate.
It achieves efficient oxidation and degradation of phenolic pollutants, has good water purification effect, and is simple and economical, avoiding secondary pollution.
Smart Images

Figure CN119524830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenol pollutant treatment, and in particular to a method for preparing a Fenton-like catalyst by utilizing chestnut shells and application of the catalyst in water purification. Background Art
[0002] Phenols are one of the most important organic pollutants in industrial wastewater in the world today. They are used in many industrial fields such as coal gas, coking, oil refining, metallurgy, machinery manufacturing, glass, petrochemicals, wood fiber, chemical organic synthesis, plastics, medicine, pesticides, paints, etc. Toxic phenol pollutants, led by phenol, can enter the human body through skin contact, oral ingestion, and inhalation, and cause hazards including tissue damage and endocrine disruption. They are relatively stable in water bodies and can continue to threaten the environment through migration, adsorption, and volatilization. In addition, depending on the different substituted functional groups, phenol pollutants may show different sensitivities to the same treatment method. Therefore, choosing a comprehensive and efficient degradation process is an important environmental protection issue.
[0003] Advanced oxidation technology activates ozone and peroxides by adding external energy or catalyst to generate hydroxyl radicals (·OH) and sulfate radicals (·SO4 - ) and singlet oxygen ( 1 O2) and other active substances to oxidize and degrade organic pollutants in water. It is widely used in the field of environmental protection due to its strong oxidation ability, high efficiency and small footprint. Selecting an efficient, green and economical catalyst can greatly improve the efficiency of the advanced oxidation process and effectively reduce secondary pollution, so it is widely used in the field of environmental protection.
[0004] At present, the commonly used metal ion and oxide catalytic advanced oxidation methods at home and abroad have harsh reaction conditions and will produce secondary pollutants. The catalytic oxidation method based on carbon materials has important technical characteristics such as environmental protection, energy saving and no secondary pollution. It is an ideal water treatment method for removing phenol pollutants. As an emerging catalyst material in recent years, carbon materials have unique advantages in the field of advanced oxidation: first, compared with the traditional Fenton process, the advanced oxidation process catalyzed by carbon materials can be completed under relatively mild conditions, which not only simplifies the process design but also saves costs; secondly, carbon materials will not leak metal during the reaction process like metal or metal oxide catalysts, which will lead to secondary pollution. Many carbon-based materials such as graphene, carbon nanotubes, and nanodiamonds have been proven to have the function of catalytic activation of persulfate. Among them, pyrolytic carbon has received widespread attention due to its diverse access, low price and excellent catalytic activity.
[0005] In recent years, with the development of agricultural economy, chestnut production has reached millions of tons, and the large amount of chestnut shells produced has become a source of solid waste that cannot be ignored. At present, the resource utilization of chestnut shells is very limited, mainly as biofuels and compost. Therefore, it is of great practical significance to find an efficient way to utilize chestnut shells. Chestnut shells are rich in lignin and cellulose and have the potential to be converted into high-quality pyrolytic carbon. However, in the resource recovery process of chestnut shells in conventional pyrolysis processes, the products after pyrolysis reaction are prone to agglomeration, the pyrolysis products are too dense, the specific surface area decreases, and the number of effective active sites is limited, resulting in low functional application potential such as adsorption and catalytic activity. This is mainly because the adsorption and catalytic activity of pyrolytic carbon mainly come from the oxygen-containing functional groups on its widely exposed graphitized surface and the surface and subsurface structural defects. These active sites can not only activate hydrogen persulfate to generate active substances, but also mediate the electron conduction from the adsorbed pollutants to hydrogen persulfate through the surface of carbon materials, thereby achieving the oxidation of organic pollutants. As far as advanced oxidation enhancement is concerned, the preparation of catalysts with high catalytic performance is one of the current mainstream research directions. The method of preparing efficient pyrolysis carbon catalysts by introducing active sites in a simple and economical way needs to be further promoted.
[0006] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0007] The purpose of the present invention is to solve the problem of how to prepare efficient pyrolytic carbon as a Fenton-like catalyst for degrading phenolic pollutants by introducing active sites in a simple and economical way, and to provide a method for preparing a Fenton-like catalyst using chestnut shells and its application in water purification.
[0008] In order to achieve the above object, the present invention discloses a method for preparing a Fenton-like catalyst using chestnut shells, comprising the following steps:
[0009] S1, calcining chestnut shells under a nitrogen atmosphere, mixing the obtained product with a strong base solid powder and grinding the mixture;
[0010] S2, calcining the mixture obtained in step S1 under a nitrogen atmosphere, and drying the obtained product after being fully washed to obtain alkali-activated chestnut shell pyrolysis carbon, i.e., a Fenton-like catalyst.
[0011] In the step S1, the calcination temperature is 400° C., the calcination time is 1.0 h to 10.0 h, the mass ratio of the product obtained after calcination to the strong base solid powder is 1:4 to 4:1, and the grinding time is 0.5 h to 3.0 h.
[0012] In the step S2, the calcination temperature is 500° C. to 800° C., and the calcination time is 1.0 h to 10.0 h.
[0013] The invention also discloses a Fenton-like catalyst prepared by the preparation method. The Fenton-like catalyst has a highly graphitized hybrid structure and is rich in surface oxygen-containing functional groups and defect sites.
[0014] The present invention also discloses the use of the above-mentioned Fenton-like catalyst in water purification, wherein the Fenton-like catalyst degrades phenolic pollutants by catalyzing hydrogen persulfate, and specifically comprises the following steps:
[0015] (1) adding hydrogen persulfate to phenol pollutants to obtain a mixed solution;
[0016] (2) adding sodium humate to the mixed solution obtained in step (1) to adjust the pH value of the catalytic degradation system to 4.0-10.0;
[0017] (3) Add a Fenton-like catalyst, stir the reaction, and then complete the catalytic degradation of phenolic pollutants.
[0018] In the step (1), the concentration of hydrogen persulfate ions in the mixed solution is 0.05 to 1 mM.
[0019] In the step (1), the concentration of phenolic pollutants is 20 mg / L.
[0020] In the step (2), the amount of sodium humate added is 0 to 30 mg / L.
[0021] In the step (3), the amount of the Fenton-like catalyst added is 0.05-0.2 g / L, the stirring speed is 500 rpm, and the reaction time is 90 min.
[0022] The phenolic pollutants are any one or more combinations of phenol, p-chlorophenol, 2,4-dichlorophenol, p-nitrophenol, o-nitrophenol and bisphenol A.
[0023] The present invention prepares chestnut shell pyrolysis carbon (Fenton-like catalyst) by two-step alkaline activation, and uses it to activate hydrogen persulfate to achieve catalytic degradation of phenolic pollutants in wastewater. The present invention introduces catalytic active sites into chestnut shell pyrolysis carbon in a structure-oriented manner through alkaline activation, and prepares an efficient Fenton-like catalyst in a simple and economical way, achieving green and efficient removal of typical phenolic pollutants in water and improving water quality safety without causing secondary pollution.
[0024] In the process of catalytic degradation, phenol pollutants are oxidized and degraded by potassium persulfate under the catalysis of alkaline-activated pyrolytic carbon through two pathways. One is that the carbonyl group on the surface of pyrolytic carbon transfers an electron to the persulfate ion to produce ·OH and ·SO4 -The second is that the phenolic pollutants adsorbed on the defect sites directly conduct two electrons to the also adsorbed hydrogen persulfate ions through the graphitized surface of the pyrolytic carbon, thereby being oxidized and decomposed.
[0025] The working principle of the present invention is that the chestnut shell pyrolysis carbon after alkali activation has a high degree of graphitization and abundant surface defects and oxygen-containing functional groups, and can therefore catalyze the oxidation of phenolic pollutants by hydrogen persulfate through both free radical and non-free radical pathways. On the one hand, hydrogen persulfate generates SO4 under the catalytic action of the carbonyl functional groups on the surface of the alkali-activated chestnut shell pyrolysis carbon. - On the other hand, alkali-activated chestnut shell pyrolysis carbon has a high degree of graphitization and abundant surface defects, which can directly mediate the two-electron conduction from adsorbed phenolic pollutants to hydrogen persulfate ions through its graphitized surface, achieving efficient oxidation of phenolic pollutants, which is a non-radical pathway.
[0026] The present invention uses potassium hydroxide to activate chestnut shell pyrolysis carbon, and uses it as a Fenton-like catalyst for a new method for efficiently catalyzing hydrogen persulfate to degrade phenolic pollutants. This new method is applicable to various types of wastewater containing phenolic pollutants, because phenolic substances are oxidized and degraded by potassium hydrogen persulfate through two pathways during the degradation process. One of them is that the carbonyl group on the surface of the pyrolysis carbon transfers an electron to the hydrogen persulfate ion to generate ·OH and ·SO4 - The first is that the phenolic pollutants adsorbed on the defect sites directly conduct two electrons to the also adsorbed hydrogen persulfate through the graphitized surface of the pyrolytic carbon, thereby being oxidized and decomposed (non-radical pathway). This mixed pathway degradation has stronger water quality adaptability and degradation efficiency.
[0027] Compared with the prior art, the beneficial effects of the present invention are:
[0028] 1. The present invention is structure-oriented and aims to introduce active sites that can efficiently activate hydrogen persulfate. It selectively uses an alkali activation method to reuse chestnut shell solid waste, and prepares it into pyrolytic carbon with excellent catalytic performance for organic wastewater treatment. It not only provides a new solid waste regeneration method, but also provides an economical way to improve the efficiency of water treatment processes, and also provides a reference for the design and preparation of related catalysts.
[0029] 2. The present invention uses a two-step alkaline activation method to prepare chestnut shell pyrolytic carbon. The prepared pyrolytic carbon has an extremely high specific surface area, abundant oxygen-containing functional groups and defect sites. These structural characteristics give the prepared pyrolytic carbon catalyst an extremely high catalytic activation efficiency of hydrogen persulfate;
[0030] 3. The alkali-activated chestnut shell pyrolysis carbon prepared by the present invention is a carbon material with the characteristics of abundant raw materials, low price, simple preparation, green environmental protection, safety and non-toxicity, and its overall structure is stable and will not cause secondary water pollution, making the present invention economically feasible and environmentally friendly;
[0031] 4. The pyrolytic carbon catalyst used in the present invention has a clear structure, rich active sites, excellent catalytic performance, and a simple treatment process. It can be applied to phenol pollutants of various types and concentrations and has good practical prospects.
[0032] 5. The present invention utilizes the structural characteristics of alkali-activated pyrolytic carbon with high graphitization degree, rich oxygen-containing functional groups and surface defects, and catalyzes persulfate degradation of pollutants through a mixed pathway. This method has a higher oxidation intensity for phenolic pollutants than a simple non-free radical pathway, and its anti-interference ability and oxidant utilization efficiency are higher than those of the traditional free radical pathway, making the overall process more applicable and stable, greatly improving the overall treatment efficiency of phenolic wastewater, and providing a new idea for advanced oxidation treatment of organic wastewater;
[0033] 6. The Fenton-like catalyst prepared from chestnut shells obtained in the present invention has a significant effect in degrading phenolic pollutants, and is of great significance in the recycling and reuse of biomass solid waste, the efficient removal of phenolic pollutants in sewage, and the production of advanced oxidation catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The scanning electron microscope images of the alkali-activated chestnut shell pyrolytic carbon prepared in Example 1, wherein (a-f) are the structural morphology of the prepared alkali-activated chestnut shell pyrolytic carbon, and (g-l) are the elemental composition of the alkali-activated chestnut shell pyrolytic carbon;
[0035] Figure 2 This is a scanning electron microscope image of a comparative product of the alkali-activated chestnut shells in Example 1 without alkali activation;
[0036] Figure 3 Comparison diagram of N2 isothermal adsorption-desorption curve, pore size distribution, Fourier transform infrared spectrum (FTIR), and electrochemical impedance spectroscopy (EIS) curve of chestnut shell pyrolysis products under different preparation conditions in Example 1;
[0037] Figure 4 (a) is the phenol degradation performance of the biochar obtained at different activation temperatures in Example 2; Figure 5 (b) is a comparison chart of the activity of KBC800 and other common catalysts in Example 2;
[0038] Figure 5Comparative test results of electrochemical linear scan LSV (a, b), cyclic voltammetry CV (c) and chronoamperometry it (d) of alkali-activated KBC800 and BC800 without alkali activation in Example 2;
[0039] Figure 6 The changes of pollutant concentration with degradation time under different catalytic systems and test conditions in Example 2, wherein (a) and (b) are the changes of phenol with degradation time under different catalyst concentrations in two catalytic systems in Example 2; (c) is the change of phenol with time under different PMS concentrations in Example 2; (d) is the change of phenol with time under different pH conditions in Example 3;
[0040] Figure 7 The degradation rates of different phenolic pollutants by alkali-activated KBC800 in Example 4 are compared.
[0041] Figure 8 The figure shows the comparison of phenol degradation rate of alkali-activated KBC800 at different cycle times and after regeneration in Example 5.
[0042] Fig. 9 This is a comparison chart of the degradation rates of phenol, a typical target pollutant in actual water samples under different test conditions in Example 6, wherein (a) is the degradation efficiency of 0.1 g / L chestnut shell pyrolysis carbon KBC800 and 1.0 mM PMS; (b) is the degradation efficiency under 0.2 g / L chestnut shell pyrolysis carbon KBC800 and 2.0 mM PMS. DETAILED DESCRIPTION
[0043] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0044] Example 1
[0045] Preparation of alkali activated chestnut shell pyrolysis carbon
[0046] The pyrolytic carbon catalyst used in this embodiment is alkali-activated chestnut shell pyrolytic carbon, which has a high specific surface area and a highly porous structure, a high degree of surface graphitization, and abundant surface defects and oxygen-containing functional groups. The preparation method is as follows: the chestnut shell is calcined at 400°C in a tube furnace under a nitrogen atmosphere for 2.0 hours, and the obtained product is mixed with potassium hydroxide at a mass ratio of 1:4 and ground for 0.5 hours; the obtained mixture is calcined at 500°C, 600°C, 700°C, and 800°C in a tube furnace under a nitrogen atmosphere for 2.0 hours, and the obtained product is fully washed and dried to obtain the alkali-activated chestnut shell pyrolytic carbon, which is recorded as KBC500, KBC600, KBC700, and KBC800 respectively.
[0047] Figure 1This is a scanning electron microscope image of the alkali-activated chestnut shell pyrolysis carbon prepared in this example. Figure 1 (a~f) are the structural morphologies of the prepared alkali-activated chestnut shell pyrolysis carbons. Figure 1 (g~l) is the elemental composition of the prepared alkali-activated chestnut shell pyrolysis carbon.
[0048] Figure 2 This is a scanning electron microscope structural morphology image of the intermediate product BC800 after pyrolysis at 800°C and without alkali activation in the process of preparing alkali-activated chestnut shells in this example. The two show completely different microscopic morphologies and pore structures.
[0049] Figure 3 (a, b) are the N2 isothermal adsorption-desorption curves and pore size distribution diagrams of chestnut shells prepared under different conditions. The pore size distribution and specific surface area of the material were measured using nitrogen adsorption-desorption technology, and the results were measured using the Autosorb-IQ3 gas adsorption instrument of Quantachrome Instruments. (c) is the Fourier transform infrared spectra of chestnut shells prepared under different conditions, which were tested on a Nicolet iS10 Fourier transform infrared spectrometer. When measuring biochar samples, the samples were mixed and ground with fully dried potassium bromide and then measured using the tableting method. (d) is the electrochemical impedance spectrum test diagram of chestnut shells prepared under different conditions. The electrolyte used was 0.1M sodium sulfate solution, the test voltage was the open circuit potential during the test, and the test frequency range was 0.1Hz to 1×105Hz.
[0050] By comparison Figure 1 , Figure 2 and Figure 3 (a) Figure 3 (b) It can be found that alkaline activation greatly changes the structural characteristics of biochar and leads to a significant increase in its specific surface area and porosity. This is mainly due to the large amount of corrosive gases produced by KOH under high temperature conditions. The expansion and erosion of these gases cause the biochar to produce a complex pore structure during the pyrolysis process, thereby increasing its specific surface area.
[0051] pass Figure 3 (c) It can be seen that a large number of oxygen functional groups were introduced into the carbon network during the KOH thermal corrosion process, that is, the -OH and CO peaks of KBC800 were more obvious than those of BC800. The large presence of oxygen-containing groups indicates that alkaline activation plays an important role in the heterogeneous catalysis of cyclic pyrolysis of chestnut shells. Figure 3 (d) further shows that KBC800 has a smaller capacitive reactance, which means that its surface carbon grid structure has less obstacles to absorbing and releasing electrons.
[0052] Example 2
[0053] Comparison of catalytic activity of alkali-activated chestnut shell pyrolysis carbon in the degradation of phenolic pollutants using persulfate (PMS) and the influence of key experimental parameters
[0054] 1. In order to verify the effect of alkali-activated chestnut shell pyrolysis carbon catalyst preparation temperature in the PMS degradation of phenolic pollutants system, four experimental systems were set up:
[0055] First, at room temperature, in a 200.0mL beaker, add 100.0mL ultrapure water to disperse phenol in deionized water to a dispersion concentration of 20.0mg / L; then, add PMS to the beakers of the four experimental systems to a concentration of 1.0mM, and add KBC500, KBC600, KBC700, and KBC800 to a concentration of 0.1g / L. The resulting systems were mixed evenly under magnetic stirring and reacted for 90.0min. During the reaction, samples were taken to detect the concentration of pollutants.
[0056] from Figure 4 (a) It can be seen that with the increase of activation temperature, the adsorption and degradation properties of biochar are significantly improved, which is due to the increase in specific surface area brought about by alkaline activation, as well as the introduction of surface defects and oxygen-containing functional groups that can serve as catalytic and adsorption sites.
[0057] 2. In order to verify the influence of different catalysts in the degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon over PMS, four experimental systems were set up:
[0058] First, at room temperature, in a 200.0mL beaker, add 100.0mL ultrapure water, disperse phenol in deionized water, and disperse to a concentration of 20.0mg / L; then, add PMS to the beakers of the four experimental systems to a concentration of 1.0mM, and add KBC800, BC800 (conventional pyrolytic carbon calcined at 800℃, no alkali activation modification process), graphite powder, multi-walled carbon nanotubes, cobalt tetraoxide, and nano zero-valent iron to a concentration of 0.1g / L. The obtained systems were mixed evenly under magnetic stirring and reacted for 90.0min. During the reaction, samples were taken to detect the concentration of pollutants.
[0059] from Figure 4 (b) It can be seen that in the comparison of the catalytic activity of KBC800 with other common metal and non-metal catalysts, it can be seen that its efficiency in catalyzing the degradation of phenol by PMS far exceeds that of the selected reference, which proves the superiority of its catalytic efficiency.
[0060] Figure 5For the comparison of multiple groups of measurements between KBC800 and BC800 in electrochemical experiments, the electrochemical workstation CHI760E model of Shanghai Chenhua Company was used with a three-electrode system, in which the reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum wire electrode, and the working electrode was a standard glassy carbon electrode with a diameter of 3 mm. Chemical tests included cyclic voltammetry (CV), linear sweep voltammetry (LSV), and chronoamperometry (IT), all of which were completed in 100 mL of electrolyte. In the CV test, the electrolyte used was 50 mM potassium ferrocyanide solution, the test voltage range was -0.2 V to 0.6 V, and the scan rate was 50 mV / s. The number of scans for each test was 10, and the data was taken after the curve morphology stabilized. In the LSV test, the electrolyte used was 0.1 M sodium sulfate solution, the test voltage range was -0.2 V to 1.0 V, and the scan rate was 50 mV / s. When the test requires the addition of PMS or pollutants, they should be added to the reaction system in advance and mixed evenly. In the it test, the electrolyte used was 0.1M sodium sulfate solution, the test time was set to 600 seconds, and 0.25mL 0.2M PMS solution and 0.25mL 4g / L phenol solution were added to the system at 200 seconds and 500 seconds respectively.
[0061] Figure 5 (a) and (b) show that when KBC800 is loaded on the electrode, the simultaneous presence of PMS and phenol produces a large current signal in the system. This may be due to the synergistic effect between the activation of PMS and the degradation of phenol, that is, the direct electron conduction between the adsorbed pollutants and PMS through the graphitized grid, while no similar synergistic effect was detected in the BC800 system. Figure 5 In (c), by comparing the CV curves of the two, it can be found that the redox peak spacing of KBC800 is smaller than that of BC800, which means that it has less hindrance to electron transfer, which is more conducive to surface-mediated electron transfer. Figure 5 (d) It can be seen that when PMS was added to the system, the KBC800 system detected an obvious current signal, while the BC800 system had no obvious response to PMS. This current signal represents the electron transfer between KBC800 and PMS and the generation of ROS. The comparison test results of electrochemical linear scan LSV, cyclic voltammetry CV and chronoamperometry it of alkali-activated KBC800 and BC800 without alkali activation further revealed the excellent interfacial charge transfer ability and multiphase Fenton-like catalytic activity of KBC800 under the optimal activation and pyrolysis conditions.
[0062] 3. In order to verify the effect of pyrolysis carbon catalyst concentration in the degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon over PMS, three experimental systems were set up:
[0063] First, at room temperature, in a 200.0mL beaker, 100.0mL of ultrapure water was added to disperse phenol in deionized water with a dispersion concentration of 20.0mg / L; then, in the first set of experimental systems, PMS was added to the beaker to a concentration of 1.0mM; in the second set of experimental systems, PMS was added to the beaker to a concentration of 1.0mM, and chestnut shell pyrolytic carbon was added to a concentration of 0.05g / L; in the third set of experimental systems, PMS was added to the beaker to a concentration of 1.0mM, and chestnut shell pyrolytic carbon was added to a concentration of 0.1g / L; in the fourth set of experimental systems, PMS was added to the beaker to a concentration of 1.0mM, and chestnut shell pyrolytic carbon was added to a concentration of 0.2g / L; finally, the obtained systems were mixed evenly under magnetic stirring and reacted for 90.0min, and samples were taken during the reaction to detect the concentration of pollutants.
[0064] Figure 6 (a), (b) show the changes of phenol concentration with degradation time in the first experimental system (without pyrolysis carbon catalyst), the second experimental system (with 0.05g / L chestnut shell pyrolysis carbon), the third experimental system (with 0.1g / L chestnut shell pyrolysis carbon), and the fourth experimental system (with 0.2g / L chestnut shell pyrolysis carbon). It can be seen that when there is no alkali-activated chestnut shell pyrolysis carbon catalyst in the system, PMS has no ability to remove phenol, but when alkali-activated chestnut shell pyrolysis carbon exists, the degradation effect of phenol is significantly enhanced with the increase of added catalyst.
[0065] 4. In order to verify the effect of PMS concentration in the degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon, the following five groups of experiments were set up:
[0066] First, at room temperature, in a 200.0mL beaker, 100.0ml of ultrapure water was added to disperse phenol in deionized water to a dispersion concentration of 20.0mg / L, and a pyrolytic carbon catalyst was added to a concentration of 0.1g / L; then, in the first set of experimental systems, PMS was added to the beaker to a concentration of 0.5mM; in the second set of experimental systems, PMS was added to the beaker to a concentration of 1.0mM; in the third set of experimental systems, PMS was added to the beaker to a concentration of 2.0mM; in the fourth set of experimental systems, PMS was added to the beaker to a concentration of 3.0mM; in the fourth set of experimental systems, PMS was added to the beaker to a concentration of 6.0mM; finally, the obtained systems were mixed evenly under magnetic stirring and reacted for 90.0min, and samples were taken during the reaction to detect the concentration of pollutants.
[0067] Figure 6(c) shows the effect of PMS concentration on the catalytic degradation efficiency of phenol under selected catalyst (0.1g / L) and pollutant (20.0mg / L) concentrations. It can be seen from the figure that compared with 0.05mM PMS, increasing its concentration to 1mM significantly increases its degradation efficiency, but continuing to increase the PMS concentration does not continue to improve the degradation efficiency. On the contrary, the degradation rate decreases at a higher PMS concentration (6.0mM). This inhibitory effect may come from the fact that PMS itself reacts with the generated active free radical OH. The high concentration of PMS amplifies this capture effect and effectively inhibits the reaction of active free radicals with pollutants. It can be seen from the figure that the reaction degradation efficiency and oxidant utilization efficiency are the best at 1.0mM, so the reaction conditions of this system are the optimal reaction conditions.
[0068] Example 3
[0069] Effect of pH on PMS Degradation of Phenolic Pollutants Catalyzed by Alkali-activated Chestnut Shell Pyrolysis Carbon
[0070] In order to verify the effect of pH on the degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon catalyzed PMS, the following experimental system was set up:
[0071] First, at room temperature, in a 200.0mL beaker, 100.0mL ultrapure water was added to disperse phenol in deionized water to a dispersion concentration of 20.0mg / L; then, the pH of the system was adjusted to 4, 5.5, 7, 8.5, and 10 by 2% H2SO4 and 1.0M NaOH solution. Then, pyrolytic carbon catalyst was added to the beaker to a concentration of 0.1g / L and PMS to a concentration of 1.0mM; finally, the obtained systems were mixed evenly under magnetic stirring and reacted for 90.0min, and samples were taken during the reaction to detect the concentration of pollutants.
[0072] Figure 6 (d) shows the degradation capacity of selected chestnut shell pyrolysis carbon (0.1g / L) and PMS (1.0mM) concentrations for pollutants (20.0mg / L) at different pH values. As can be seen from the figure, the adsorption capacity of chestnut shell pyrolysis carbon for pollutants increases with the increase of pH value, and it has obvious degradation and removal ability for pollutants in a wide pH range. The reason may be that PMS is more easily activated under alkaline conditions, and the concentration of hydrogen ions captured by active free radicals is reduced, which is more conducive to its reaction with pollutants. The experimental results show that this method has high applicability and can be used for wastewater treatment under various pH conditions.
[0073] Example 4
[0074] Determination of the degradation efficiency of various phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon catalyzed PMS degradation system
[0075] In order to verify the influence of the types of phenolic pollutants in the degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon over PMS, the following experimental system was set up:
[0076] First, at room temperature, in a 200.0mL beaker, 100.0mL of ultrapure water was added, and phenol, 4-chlorophenol (4-CP), p-nitrophenol (PNP), 2,4-dichlorophenol (2,4-DCP), ortho-nitrophenol (ONP) and bisphenol A (BPA) were dispersed in deionized water with a dispersion concentration of 20.0mg / L; then, PMS was added to the beaker to a concentration of 1.0mM; finally, pyrolytic carbon catalyst was added to a concentration of 0.1g / L, and the resulting systems were mixed evenly under magnetic stirring and reacted for 90.0min. During the reaction, samples were taken to detect the concentration of pollutants.
[0077] Figure 7 The results show that the chestnut shell pyrolysis carbon catalyzed PMS degradation system has a removal efficiency of more than 80% for the selected phenolic pollutants within the selected time, which fully demonstrates the wide applicability and effectiveness of the degradation system for various phenolic pollutants.
[0078] Example 5
[0079] Cycling and regeneration experiments on degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon catalyzed by PMS
[0080] In order to verify the feasibility of the process of catalytic degradation of phenolic pollutants by alkali-activated chestnut shell pyrolysis carbon PMS and the stability and activity of the catalyst, the following experimental system was designed:
[0081] First, at room temperature, in a 200.0mL beaker, 100.0mL ultrapure water was added to disperse phenol in deionized water to a dispersion concentration of 20.0mg / L; then, PMS was added to the beaker to a concentration of 1.0mM; then, pyrolytic carbon catalyst was added to a concentration of 0.1g / L, and the resulting systems were mixed evenly under magnetic stirring and reacted for 90.0min. During the reaction, samples were taken to detect the concentration of pollutants. After the reaction, the catalyst was recovered by filtering the reaction solution, and was fully washed with ultrapure water and dried in a 60℃ oven for reuse.
[0082] Under the same conditions, the above reaction steps were repeated for four cycles, and the catalyst obtained after four reactions was placed in a tube furnace and re-calcined at 400°C for 1.0 hour under nitrogen atmosphere to complete catalyst regeneration. The obtained regenerated catalyst was subjected to catalytic degradation reaction again.
[0083] Figure 8The figure shows the comparison of phenol degradation rates under different cycle times and after regeneration. It can be seen from the figure that the catalyst can maintain a degradation efficiency of 40% when used for the fourth time, and after regeneration, its degradation efficiency can be restored to 90%. Considering the low cost of alkali-activated chestnut shell pyrolysis carbon and the simplicity of the reactivation step, this cycle experiment strongly proves the economic feasibility of the catalytic system and the stability of the catalyst.
[0084] Example 6
[0085] Degradation efficiency of phenolic pollutants in actual sewage by alkali-activated chestnut shell pyrolysis carbon catalyzed PMS
[0086] In order to verify the degradation performance of phenolic pollutants in actual sewage by alkali-activated chestnut shell pyrolysis carbon catalyzed by PMS, the following experimental system was set up:
[0087] First, at room temperature, in a 200.0mL beaker, add 100.0mL of sewage plant secondary sedimentation tank effluent, whose COD value is 168.0mg / L, and disperse phenol in it, with a dispersion concentration of 20.0mg / L; then, add PMS to the beaker to a concentration of 1.0mM or 2.0mM; then, add pyrolytic carbon catalyst to a concentration of 0.1g / L or 0.2g / L, and the resulting systems are mixed evenly under magnetic stirring and reacted for 90.0min. During the reaction, samples are taken to detect the concentration of pollutants. The operation steps of the blank control experiment are the same as above, but the reaction is carried out in ultrapure water.
[0088] Fig. 9 (a) shows the degradation efficiency of phenol under 0.1 g / L chestnut shell pyrolysis carbon and 1.0 mM PMS. It can be seen that the components in the actual sewage have a certain inhibitory effect on the degradation of phenol. This phenomenon may be caused by the competition between organic matter and phenolic pollutants for active substances, but its overall efficiency can still reach more than 80%. Fig. 9 (b) shows the degradation efficiency of phenol after increasing the chestnut shell pyrolysis carbon concentration to 0.1 g / L and the PMS concentration to 1.0 mM. The inhibitory effect almost disappears after increasing the dosage of catalyst and oxidant, proving the practicality and effectiveness of the catalytic oxidation system.
[0089] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a Fenton-like catalyst using chestnut shells, characterized in that: The following steps are involved: S1, calcining chestnut shells under a nitrogen atmosphere, mixing the obtained product with a strong base solid powder and grinding the mixture; S2, calcining the mixture obtained in step S1 under a nitrogen atmosphere, and drying the obtained product after being fully washed to obtain alkali-activated chestnut shell pyrolysis carbon, i.e., a Fenton-like catalyst.
2. A method for preparing a Fenton-like catalyst using chestnut shells as claimed in claim 1, characterized in that: In the step S1, the calcination temperature is 400° C., the calcination time is 1.0 h to 10.0 h, the mass ratio of the product obtained after calcination to the strong base solid powder is 1:4 to 4:1, and the grinding time is 0.5 h to 3.0 h.
3. A method for preparing a Fenton-like catalyst using chestnut shells as claimed in claim 1, characterized in that: In the step S2, the calcination temperature is 500° C. to 800° C., and the calcination time is 1.0 h to 10.0 h.
4. A Fenton-like catalyst prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the Fenton-like catalyst as claimed in claim 4 in water purification, characterized in that: The Fenton-like catalyst degrades phenolic pollutants by catalyzing hydrogen persulfate, and specifically comprises the following steps: (1) adding hydrogen persulfate to phenol pollutants to obtain a mixed solution; (2) adding sodium humate to the mixed solution obtained in step (1) to adjust the pH value of the catalytic degradation system to 4.0-10.0; (3) Add a Fenton-like catalyst, stir the reaction, and then complete the catalytic degradation of phenolic pollutants.
6. The use of a Fenton-like catalyst in water purification as claimed in claim 5, characterized in that: In the step (1), the concentration of hydrogen persulfate ions in the mixed solution is 0.05 to 1 mM.
7. The use of a Fenton-like catalyst in water purification as claimed in claim 5, characterized in that: In the step (1), the concentration of phenolic pollutants is 20 mg / L.
8. The use of a Fenton-like catalyst in water purification as claimed in claim 5, characterized in that: In the step (2), the amount of sodium humate added is 0 to 30 mg / L.
9. The use of a Fenton-like catalyst in water purification as claimed in claim 5, characterized in that: In the step (3), the amount of Fenton-like catalyst added is 0.05-0.2 g / L, the stirring speed is 500 rpm, and the reaction time is 90 min.
10. Use of a Fenton-like catalyst in water purification as claimed in claim 5, characterized in that: The phenolic pollutants are any one or more combinations of phenol, p-chlorophenol, 2,4-dichlorophenol, p-nitrophenol, o-nitrophenol and bisphenol A.